Epidemiological characteristics of hand, foot and mouth disease in Pingdu, Shandong, China from 2013 to 2023 and DLNM analysis of its variation with temperature - Hua Zhang; ChangLan Yu; DaiXia Yang; Wei Zhang; ShouJie Dai; Hui Lv; Xiaolin Liu (PLoS ONE, 2025)
Background The purpose of this study is to describe the epidemiological situation of HFMD in Pingdu over the past decade, and investigate the relationship between environmental factors, specifically temperature, and the incidence of hand, foot and mouth disease. Methods S tatistical techniques, including Distributed Lag Non-linear Models and spatial autocorrelation analysis, were employed to elucidate epidemiological characteristics of hand, foot and mouth disease in Pingdu and the non-linear effects time-lagged relationships of temperature on the incidence. Results The incidence of hand, foot and mouth disease in Pingdu exhibits seasonal distribution, and the incidence rate is highest from May to August each year. The spatial distribution shows almost no spatial autocorrelation. Children under the age of 7 account for 91.09% of HFMD cases, with an obvious trend of increased incidence in older age groups by 2023. Notably, severe cases predominantly occurred in children under 3 years old, and EV-A71 accounts for a higher proportion compared with other enteroviruses. The pathogen types of hand, foot and mouth disease have changed from mainly EV-A71 and CVA16 to other enteroviruses. When the daily maximum temperature reaches 33.4°C, the relative risk (RR = 1.33) is highest at the one lag day. Conclusion This study reveals the epidemiological characteristics and climate risk factors of hand, foot and mouth disease in Pingdu. It is important to note that children, especially those under the age of 3, are the key population for the prevention and control of hand, foot and mouth disease. It is recommended that health authorities incorporate temperature into the formulation of hand, foot and mouth disease prevention and control policies.